Molecular mechanism of Danshenol C in reversing peritoneal fibrosis: novel network pharmacological analysis and biological validation - Jiabin Liang; Lulu Cheng; Jie Feng; Zeping Han; Chen Huang; Fangmei Xie; Yongsheng Li; Xun Luo; Qingmei Wang; Jinhua He; Hanwei Chen (BMC, 2023)
Abstract Objective The primary objective of this study is to elucidate the molecular mechanism underlying the reversal of peritoneal fibrosis (PF) by Danshenol C, a natural compound derived from the traditional Chinese medicine Salvia miltiorrhiza. By comprehensively investigating the intricate interactions and signaling pathways involved in Danshenol C's therapeutic effects on PF, we aim to unveil novel insights into its pharmacological actions. This investigation holds the potential to revolutionize the clinical application of Salvia miltiorrhiza in traditional Chinese medicine, offering promising new avenues for the treatment of PF and paving the way for evidence-based therapeutic interventions. Methods Firstly, we utilized the YaTCM database to retrieve the structural formula of Danshenol C, while the SwissTargetPrediction platform facilitated the prediction of its potential drug targets. To gain insights into the genetic basis of PF, we acquired the GSE92453 dataset and GPL6480-9577 expression profile from the GEO database, followed by obtaining disease-related genes of PF from major disease databases. R software was then employed to screen for DEG associated with PF. To explore the intricate interactions between Danshenol C's active component targets, we utilized the String database and Cytoscape3.7.2 software to construct a PPI network. Further analysis in Cytoscape3.7.2 enabled the identification of core modules within the PPI network, elucidating key targets and molecular pathways critical to Danshenol C's therapeutic actions. Subsequently, we employed R to perform GO and KEGG pathway enrichment analyses, providing valuable insights into the functional implications and potential biological mechanisms of Danshenol C in the context of PF. To investigate the binding interactions between the core active components and key targets, we conducted docking studies using Chem3D, autoDock1.5.6, SYBYL2.0, and PYMOL2.4 software. We applied in vivo and in vitro experiments to prove that Danshenol C can improve PF. In order to verify the potential gene and molecular mechanism of Danshenol C to reverse PF, we used quantitative PCR, western blot, and apoptosis, ensuring robust and reliable verification of the results. Results ① Wogonin, sitosterol, and Signal Transducer and Activator of Transcription 5 (STAT5) emerged as the most significant constituents among the small-molecule active compounds and gene targets investigated. ②38 targets intersected with the disease, among which MAPK14, CASP3, MAPK8 and STAT3 may be the key targets; The results of GO and KEGG analysis showed that there was a correlation between inflammatory pathway and Apoptosis. ④Real-time PCR showed that the mRNA expressions of MAPK8 (JNK1), MAPK14 (P38) and STAT3 were significantly decreased after Danshenol C treatment (P < 0.05), while the mRNA expression of CASP3 was significantly increased (P < 0.05)⑤Western blot showed that protein expressions of CASP3 and MAPK14 were significantly increased (P < 0.05), while the expression of STAT3 and MAPK8 was decreased after Danshenol C treatment (P < 0.05). ⑥There was no significant difference in flow analysis of apoptosis among groups. Conclusion The findings suggest that Danshenol C may modulate crucial molecular pathways, including the MAPK, Apoptosis, Calcium signaling, JAK-STAT signaling, and TNF signaling pathways. This regulation is mediated through the modulation of core targets such as STAT3, MAPK14, MAPK8, CASP3, and others. By targeting these key molecular players, Danshenol C exhibits the potential to regulate cellular responses to chemical stress and inflammatory stimuli. The identification of these molecular targets and pathways represents a significant step forward in understanding the molecular basis of Danshenol C's therapeutic effects in PF. This preliminary exploration provides novel avenues for the development of anti-PF treatment strategies and the discovery of potential therapeutic agents. By targeting specific core targets and pathways, Danshenol C opens up new possibilities for the development of more effective and targeted drugs to combat PF. These findings have the potential to transform the landscape of PF treatment and offer valuable insights for future research and drug development endeavors.